Rozwój przedsiębiorczości na obszarach wiejskich problemowych - Kurek, Iwona Małgorzata (Entrepreneurship Development at Rural Problem Areas, 2005)
Results of the research carried within 114 communes in Warmia-Mazury region, mainly concerning unemployment, levels of education and technical infrastructure as well as their strategic priorities are presented in the paper. Local self-governments ought to implement activities in order to increase attractiveness of the region for potential investors not only by improvement of the level of infrastructure and communication, but also development of the base for business (i.e. banks, insurance firms). However, many communes' leaders have still been treating their units as typical agricultural ones and see no point in any activities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 538-544